2003
DOI: 10.1677/joe.0.1790063
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of glucose transporter 8 in rat Leydig cells

Abstract: Basal and LH/human chorionic gonadotropin (hCG)-stimulated testosterone formation by Leydig cells is dependent on ambient glucose levels. Inhibition of glucose uptake is associated with decreased testosterone formation. Recently, glucose transporter 8 (GLUT8) has been shown to be highly expressed in the testis. In the present study, we have investigated the expression and regulation of the GLUT8 gene in rat Leydig cells. Primers were designed by using sequences that are not conserved in GLUT1 to GLUT5 and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…We have also reported that SLC2A9 protein expression was significantly increased in the kidney and liver from STZinduced diabetic mice compared with non-diabetic mice (Keembiyehetty et al 2006). Although SLC2A8 (Ibberson et al 2002, Schurmann et al 2002, Chen et al 2003, Gomez et al 2006, Kim & Moley 2007) and SLC2A9 (Kim & Moley 2007) are expressed in the testis and sperm, it is not known whether their expression or localization is altered in the diabetic male reproductive system or not. The objective of this study was to determine whether sperm quality, fertilization capacity, and subsequent embryo development are altered in diabetic male mice and whether differences in facilitative glucose transporter (SLC2A) expression in the testis and sperm exist.…”
Section: Introductionmentioning
confidence: 94%
“…We have also reported that SLC2A9 protein expression was significantly increased in the kidney and liver from STZinduced diabetic mice compared with non-diabetic mice (Keembiyehetty et al 2006). Although SLC2A8 (Ibberson et al 2002, Schurmann et al 2002, Chen et al 2003, Gomez et al 2006, Kim & Moley 2007) and SLC2A9 (Kim & Moley 2007) are expressed in the testis and sperm, it is not known whether their expression or localization is altered in the diabetic male reproductive system or not. The objective of this study was to determine whether sperm quality, fertilization capacity, and subsequent embryo development are altered in diabetic male mice and whether differences in facilitative glucose transporter (SLC2A) expression in the testis and sperm exist.…”
Section: Introductionmentioning
confidence: 94%
“…In spite of the fact that it is mainly expressed in testis, with a possible function of glucose and fructose transport, the precise localization of this protein in testicular cells remains unclear and controversial. It has been reported that GLUT8 expression is restricted to the type I spermatocytes in the rat (Ibberson et al 2002), in the innermost cells within the seminiferous tubules and spermatozoa in mice and man (Schü rmann et al 2002), and in rat Leydig cells (Chen et al 2003). It has also been reported that GLUT8 seems to be hormonally regulated in testis, since it is detected neither in testicular carcinoma nor under estrogen treatment (Doege et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The proteins of the media were then concentrated by precipitation with cold acetone and dissolved in ice-cold lysis buffer. The CXCL10 protein in the concentrated cell medium was detected by Western blot analysis, as described previously (Chen et al 2003). Recombinant rat CXCL10 (Santa Cruz Biotechnology, Santa Cruz, CA, USA) was used as a positive control.…”
Section: Western Blot Analysismentioning
confidence: 99%